The Implementasi Manajemen Risiko Pada Warung Internet CYBERNETIC PC GAMING Dengan Menggunakan NIST 800-30: Manajemen resiko - Rizky Alberto Evangelista Pardede; Ucu Nugraha (LP2M Universitas Widyatama, 2025)
The operational dependency of internet cafes (gaming centers) on Information Technology (IT) infrastructure creates significant risk exposure to business continuity and data security. Cybernetic PC Gaming, a gaming service provider in Bandung, faces challenges in the form of cyber threats and physical disruptions that have the potential to damage its reputation and financial standing. This study aims to identify, analyze, and evaluate the level of information security risk by applying the National Institute of Standards and Technology (NIST) Special Publication 800-30 framework. The research method employed is descriptive qualitative, encompassing the nine stages of risk management, from system characterization to mitigation results documentation. The study successfully identified five primary risk profiles. Based on risk matrix calculations, two threats were classified at a